The Work Experience of Newly Recruited Male Nurses during COVID-19: A Qualitative Study - Huiyue Zhou; Xin Wang; Ruofei Du; Xiang Cheng; Kexin Zheng; Shiqi Dong; Justin Henri; Changying Chen; Tao Wang (Elsevier, 2021)
ABSTRACT: Purpose: This study was to investigate the work experience of newly recruited male nurses during the COVID-19 pandemic. Methods: With a phenomenological approach, this qualitative study was adopted semistructured interviews by phone or video calls. A total of 9 male nurses newly recruited for the COVID-19 wards in Chinese hospitals were interviewed for this study. And Colaizzi's method was applied for evaluation in the data analysis. Results: Based on our findings, three themes were extracted. First, the newly recruited male nurses showed negative emotions at the beginning of COVID-19 epidemic, which was caused by changes in working conditions and content, but also prompted the nurses to change the way of coping with the crisis. Second, they gradually mastered the working skills and psychological training to cope with COVID-19 and developed a positive attitude toward life and a high sense of professional responsibility. Finally, we learned about their needs to respond to public health emergencies such as the COVID-19 pandemic. Conclusion: COVID-19 is a disaster for all of humanity. The newly recruited male nurses are an important force in emergency rescue. Although they suffered from short-term negative emotions, they quickly adapted to the crisis. In order to better prepare for future emergencies, the disaster response capacity of newly recruited male nurses needs to be further improved. In addition, newly recruited male nurses have a strong demand for timely and personalized career development guidance.